Laboratory biosafety in China: past, present, and future - Wu, Guizhen (Biosafety and health, 2019)
The launch of the new journal, Biosafety and Health, presents me with a unique opportunity to recount the progress of laboratory biosafety (LB) in China and my contribution to this area over the past 30 years. Since the severe acute respiratory syndrome epidemic in 2003, China has constructed a primary network of high-level biosafety laboratories at different levels and established an expert team on LB. Furthermore, a series of LB management documents, including laws, regulations, standards, and guidelines, have been developed and published. This gradually maturing LB system has played a pivotal role in emerging infectious disease control and prevention, as well as in research, which in turn contributes to public health. In recent years, international collaboration between China and other countries has also been accelerated. Despite these achievements, we are still facing many challenges and opportunities in the field of LB. Sustainable LB development requires the joint efforts of the entire society and continuous international cooperation to safeguard global public health. •Since the SARS epidemic, China has constructed a biosafety laboratories network and set up an expert team on LB.•A series of LB management documents, including laws, regulations, standards, and guidelines, have been published.•In recent years, international collaboration between China and other countries has also been accelerated.•In future, infrastructure, regulatory system and human resource should be enhanced to improve China’s LB system.